Open and Arthroscopic Triangular Fibrocartilage Complex (TFCC) Repair. Issue 12 (15th June 2021) - Srinivasan, Ramesh C.; Shrouder-Henry, Jason J.; Richard, Marc J.; Ruch, David S.
Abstract : Triangular fibrocartilage complex (TFCC) tears, whether acute or chronic, can result in persistent ulnar-sided wrist pain. Although diagnosis and nonsurgical management of TFCC tears is well described, there remains ongoing discussion about the optimal surgical technique, specifically open or arthroscopic. This article reviews the most up-to-date literature regarding TFCC injury including demographics, risk factors for TFCC injury, classification of acute and chronic TFCC tears, history and physical examination, appropriate diagnostic imaging, surgical indications, pertinent surgical anatomy, open and arthroscopic TFCC repair, fixation biomechanics and techniques, postoperative rehabilitation, and clinical outcomes.